2001
DOI: 10.1016/s0002-9440(10)64033-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase-2 in Human Transitional Cell Carcinoma of the Urinary Bladder

Abstract: Recent studies suggest that expression of cyclooxygenase-2 (Cox-2) is elevated in transitional cell carcinoma (TCC) of the urinary bladder and that inhibition of Cox-2 activity suppresses bladder cancer in experimental animal models. We have investigated the expression of Cox-2 protein in human TCCs (n = 85), in in situ carcinomas (Tis) of the urinary bladder (n = 17), and in nonneoplastic urinary bladder samples (n = 16) using immunohistochemistry. Cox-2 immunoreactivity was detected in 66% (67 of 102) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
229
3
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(246 citation statements)
references
References 22 publications
12
229
3
2
Order By: Relevance
“…[45][46][47] Although one study reported that COX-2 expression was positively correlated with ROI production and decreased by antioxidants, 48,49 the present study indicated that COX-2 expression was decreased by Mn-SOD antisense in correlation with Bcl-2 expression. The mechanism of the decrease of COX-2 expression is not clear, but high levels of NO have been reported to suppress COX-2 expression.…”
Section: Discussionmentioning
confidence: 61%
“…[45][46][47] Although one study reported that COX-2 expression was positively correlated with ROI production and decreased by antioxidants, 48,49 the present study indicated that COX-2 expression was decreased by Mn-SOD antisense in correlation with Bcl-2 expression. The mechanism of the decrease of COX-2 expression is not clear, but high levels of NO have been reported to suppress COX-2 expression.…”
Section: Discussionmentioning
confidence: 61%
“…10,38 Although the potential therapeutic efficacy of NSAIDs was related exclusively to tumors located in the digestive tract, some studies have suggested that COX-2 may be the target for the prevention and treatment of other carcinomas, including those of the prostate, 8,39 breast, 13,40,41 pancreas, 12,42 head and neck, 43 and the urinary bladder. 44,45 To our knowledge, no epidemiologic studies have been performed to determine the protective effects of COX-2 inhibitors on the development and progression of pituitary tumors. Our observations of higher COX-2 expression in pituitary tumor specimens compared with normal tissue specimens are consistent with previous findings reporting COX-2 overexpression in tumor specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulative evidence has shown that overexpression of cyclooxygenase-2 (COX-2) in gastric adenocarcinoma might play a crucial role in invasive tumor growth and offer a new strategy against cancer by the use of COX-2 inhibitors. [1][2][3][4] The inhibitive effect of aspirin or rofecoxib, a higher selective COX-2 inhibitor 5 on the proliferation of gastric cancer, has been observed in our previous studies. 6,7 Various studies have demonstrated that the growth of normal cells and malignant tumor may be regulated by gut peptides.…”
mentioning
confidence: 83%
“…Interaction of the 2 drugs is quantitatively determined by the combination index (CI), which is calculated as follows: 2 , where D X is the dose that is required to produce X% inhibition of 3 H-TdR incorporation. When CI ϭ 1, summation is indicated; when CI Ͻ 1, synergism is indicated; when CI Ͼ 1, antagonism is indicated.…”
Section: Effect Of Rofecoxib Plus Octreotide On Growth Of Gastric Canmentioning
confidence: 99%